2020
DOI: 10.1038/s41467-020-16394-3
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin 153 links nuclear pore complex to chromatin architecture by mediating CTCF and cohesin binding

Abstract: Nucleoporin proteins (Nups) have been proposed to mediate spatial and temporal chromatin organization during gene regulation. Nevertheless, the molecular mechanisms in mammalian cells are not well understood. Here, we report that Nucleoporin 153 (NUP153) interacts with the chromatin architectural proteins, CTCF and cohesin, and mediates their binding across cis-regulatory elements and TAD boundaries in mouse embryonic stem (ES) cells. NUP153 depletion results in altered CTCF and cohesin binding and differentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 70 publications
8
51
0
Order By: Relevance
“…These findings support a mechanistic model whereby NPC-anchored enhancer-promoter looping of poised genes, preserved after removal of an inductor, may facilitate more rapid reactivation of these genes in response to external stimuli [ 16 ] ( Figure 3 c). A similar model was recently suggested to explain rapid activation of immediate early gene transcription in response to an induction by epidermal growth factor in HeLa cells [ 81 ]. In this case, the NPC-linked Nup153 controls binding of CTCF and cohesin with the promoter and enhancer of uninduced gene, leading to RNA polymerase II pausing on its promoter.…”
Section: Influence Of Elys and Other Nups On Gene Expressionmentioning
confidence: 78%
See 2 more Smart Citations
“…These findings support a mechanistic model whereby NPC-anchored enhancer-promoter looping of poised genes, preserved after removal of an inductor, may facilitate more rapid reactivation of these genes in response to external stimuli [ 16 ] ( Figure 3 c). A similar model was recently suggested to explain rapid activation of immediate early gene transcription in response to an induction by epidermal growth factor in HeLa cells [ 81 ]. In this case, the NPC-linked Nup153 controls binding of CTCF and cohesin with the promoter and enhancer of uninduced gene, leading to RNA polymerase II pausing on its promoter.…”
Section: Influence Of Elys and Other Nups On Gene Expressionmentioning
confidence: 78%
“…However, as a dynamic Nup [ 22 ], it may also interact with chromatin in the nuclear interior. Mapping of Nup153-interacting regions in mammalian genomes by DamID or ChIP-seq has shown that, depending on cell type, Nup153 may interact with the active H3K27 acetylated chromatin of super enhancers [ 15 ], with the inactive Pc-repressed chromatin of developmental genes [ 14 ], with the promoters and 3′-ends of Sox2-regulated genes [ 80 ], or with active and inactive promoters, as well as with enhancers and boundaries between topologically associating domains (TADs) [ 81 ]. Nup153-genome interactions take place both at the NE and in the nucleoplasm.…”
Section: Genome-wide Interactions Of Elys and Other Nupsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a critical role in transcription has been assigned to components of the nuclear pore basket, which are closest to the the genome [11,[23][24][25][26], gene expression has also been reported to depend on the core NPC scaffold [9,27,28], including the Y-complex (a.k.a. the Nup84 complex in budding yeast).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Y-complex Nup components ELYS and Sec13 (Figure 2 ) can alter chromatin functionality via interacting with chromatin remodeling complexes ( 169 ). Nup153 was recently shown to effect chromatin organization via interacting with architectural proteins CTCF (CCCTC-binding factor) and cohesion ( 170 ). Given that Nup153 and CPSF6 share the same binding pocket on CA (Figure 4C and D ), additional work is required to discern whether regulating the CA-CPSF6 interaction or perhaps a novel pathway involving CTCF/cohesion underlies Nup153’s role in HIV-1 integration site targeting.…”
Section: Introductionmentioning
confidence: 99%